Comprehensive Analysis of Acetylation-Related lncRNAs and Identified AC099850.3 as Prognostic Biomarker in Non-Small Cell Lung Cancer. (12th October 2021) - Zhou, Junliang; Zhang, Mingyan; Dong, Huanhuan; Wang, Meiqi; Cheng, Yue; Wang, Shuqing; Ma, Wenbo; Xu, Hui
Abstract : The present study aimed to analyze the effects of acetylation-related lncRNAs in non-small-cell lung cancer (NSCLC). A total of 399 differentially expressed lncRNAs (DElncRNAs) have been identified between 497 NSCLC tissues and 54 normal tissues in the TCGA database, and 105 of which were correlated with acetylation regulators. By using univariate cox regression analysis and combining it with clinical prognosis information, 12 prognostic-related lncRNAs were selected for the subsequent analysis. The NSCLC patients were divided into two subgroups (cluster 1 and cluster 2) by clustering software, and immunocyte infiltration analysis, microenvironmental analysis, and clinical relevance analysis were performed between the two subgroups. A risk model was also built to further assess the prognosis value of prognostic-related lncRNAs in NSCLC patients. We found that AC099850.3 was significantly higher in both cluster 1 and high-risk subgroups, which may serve as a potential biomarker for the prognosis of NSCLC patients. Then, based on ceRNA competition mechanisms, the pathway enrichment of 105 acetylation-related lncRNAs was conducted by GO and KEGG analyses. We found the acetylation-related lncRNAs were primarily enriched in MAPK and EGFR signaling pathways, which were closely associated with NSCLC development. Finally, we validated the expression levels of AC099850.3 in NSCLC tissues and adjacent non-cancerous tissues and confirmed that AC099850.3 was significantly highly expressed in NSCLC tissues and cells. These results may provide clues for our understanding of the role of acetylation-related lncRNAs and valuable information for future clinical diagnosis and prognosis in NSCLC patients.